Clumpy galaxies in CANDELS. II. Physical properties of UV-bright clumps at 0.5 ≤ z < 3 - Guo, Yicheng; Rafelski, Marc; Bell, Eric F.; Conselice, Christopher J.; Dekel, Avishai; Faber, S. M.; Giavalisco, Mauro; Koekemoer, Anton M.; Koo, David C.; Lu, Yu; Mandelker, Nir; Primack, Joel R.; et al. (American Astronomical Society, 2018)
Studying giant star-forming clumps in distant galaxies is important to understand galaxy formation and evolution. At present, however, observers and theorists have not reached a consensus on whether the observed "clumps" in distant galaxies are the same phenomenon that is seen in simulations. In this paper, as a step to establish a benchmark of direct comparisons between observations and theories, we publish a sample of clumps constructed to represent the commonly observed "clumps" in the literature. This sample contains 3193 clumps detected from 1270 galaxies at $0.5\leqslant z\lt 3.0$. The clumps are detected from rest-frame UV images, as described in our previous paper. Their physical properties (e.g., rest-frame color, stellar mass (M*), star formation rate (SFR), age, and dust extinction) are measured by fitting the spectral energy distribution (SED) to synthetic stellar population models. We carefully test the procedures of measuring clump properties, especially the method of subtracting background fluxes from the diffuse component of galaxies. With our fiducial background subtraction, we find a radial clump U − V color variation, where clumps close to galactic centers are redder than those in outskirts. The slope of the color gradient (clump color as a function of their galactocentric distance scaled by the semimajor axis of galaxies) changes with redshift and M* of the host galaxies: at a fixed M*, the slope becomes steeper toward low redshift, and at a fixed redshift, it becomes slightly steeper with M*. Based on our SED fitting, this observed color gradient can be explained by a combination of a negative age gradient, a negative E(B − V) gradient, and a positive specific SFR gradient of the clumps. We also find that the color gradients of clumps are steeper than those of intra-clump regions. Correspondingly, the radial gradients of the derived physical properties of clumps are different from those of the diffuse component or intra-clump regions.